The role of big-five personality and types of social media on perceived risk - Anggarani, Fadjri Kirana; Mardhiyah, Zahrina; Dewi, Claudia Rosari; Safithri, Trisnia Rizqi; Andreina, Sherly Rachma; Maisaroh, Rizqi; Pratiwi, Yovita Ajeng; Elmawati, Anjani (Universitas Muhammadiyah Surakarta, 2022)
Abstract. The infodemic spread during the last pandemic situation, and each individual's perceived risk varies based on the dominance of his/her personality. This study, therefore, aims to examine the effect of the Big-Five Personality and social media on the perceived risk in the vulnerable group. The number of subjects was 267 respondents from adolescence to late adulthood, with inclusion criteria: (1) active users of social media, (2) over 19 years old, and (3) approved informed consent. The research consisted of two study stages: quantitative and qualitative. The instruments used in the quantitative stage were (1) the social media questionnaire, (2) the Big-Five Inventory (BFI) scale, and (3) the perceived risk scale, while the instrument employed in the qualitative stage was an interview guideline with an open questionnaire. Then, quantitative data analysis used regression techniques, whereas qualitative ones utilized content technique analysis. As a result, the Big-Five Personality and the types of social media simultaneously and significantly affected perceived risk (p0.05). According to the qualitative method results, the information topic